The limits of Europe : identities, spaces, values / edited by Russell Foster and Jan Grzymski. - Foster, Russell (Russell David); Grzymski, Jan (Global discourse, 2022)
Over recent years, a series of challenges including Brexit and the rise of Euroscepticism, have manifested in landmark moments for European integration. First published as a special issue of Global Discourse, this edited collection investigates whether these crises are isolated phenomena or symptoms of a deeper malaise across the EU.